High-Risk Human Papillomavirus Oncogenic E6/E7 mRNAs Splicing Regulation - Zheng, Yunji; Li, Xue; Jiao, Yisheng; Wu, Chengjun (Frontiers in Cellular and Infection Microbiology, 2022)
High-risk human papillomavirus infection may develop into persistent infection that is highly related to various cancer progression, including cervical cancer and head and neck squamous cell carcinomas (HNSCC). The most common high-risk subtypes are HPV16 and HPV18. The oncogenic viral proteins expressed by high-risk HPVs E6/E7 are tightly involved in cell proliferation, differentiation, and cancerous transformation. Since E6/E7 mRNAs are derived from the same pre-mRNA. Hence, the alternative splicing in E6/E7 coding region affects the balance of E6/E7 expression level. Interrupting the balance of E6 and E7 levels results in cell apoptosis. Therefore, it is crucial to understand the regulation of E6/E7 splice sites selection and the interaction of splicing enhancers and silencers with cellular splicing factors. In this review, we reviewed the known splicing sites within E6/E7 coding region in high-risk HPVs and concluded the identified cis-regulatory elements, which interact with various splicing factors to control the level of E6/E7 protein.